Analisis Kebijakan Pembatasan Sosial Berskala Besar (PSBB) dalam Penanggulangan dan Pencegahan COVID-19 di Kota Depok - Labetubun, Julia Christy; Rachmawati, Anggun; Fitria, Febby Zuriani; Mukaromah, Yayu; Rachmadiah, Yudith; Pratomo, Hadi (UI Scholars Hub, 2021)
Background. COVID-19 entered Indonesia first in Depok City on 2 nd March 2020. Massive spread requires infected countries to enact strict policies. The policy chosen by Indonesia is a Large-Scale Social Restrictions Policy (PSBB). Declared as a red zone, Depok City, through the West Java Governor Decree No.443/2020, stipulates the implementation of PSBB on 15th April 2020. Objective. to identify and analyze the implementation of PSBB policies in Depok City and formulate strategic recommendations for PSBB implementation policies Method. The method used media content analysis to collect PSBB policy data in Depok City, then analyzing it using a policy triangle approach and SWOT analysis techniques. Results. There are 23 Local Government Policies to tackle COVID-19 in Depok City. Six of them implemented the PSBB and two regulations relating to the sanction for PSBB violators. The PSBB was applied in 4 stages of extension and 1 stage to continue the Proportional PSBB. Conclusion. The extension stages of PSBB policy have successfully changed to be the yellow zone with Rt = 0,54 on 8 th June 2020. Therefore, Depok City is ready to implement Proportional PSBB.